1998
DOI: 10.1212/wnl.50.6.1630
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease Improved function with GMl ganglioside treatment in a randomized placebo‐controlled study

Abstract: This study demonstrates that GM1 ganglioside treatment enhances neurologic function significantly in PD patients. Further study is warranted to evaluate long-term effects of GM1 in PD patients and to elucidate further the mechanisms underlying patient improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 2 publications
2
39
0
Order By: Relevance
“…Our treatment schedule has been valuable for patients with AD: the disappearance of Parkinson-like symptoms in a few weeks, the significant increase in dopamine turnover and the beneficial effect of parenteral administration of GM1 to patients with Parkinson's disease [24] suggest that our treatment method will be particularly useful for patients with Parkinson's disease. It is our sincere hope that other research groups will take note of these findings and extend our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Our treatment schedule has been valuable for patients with AD: the disappearance of Parkinson-like symptoms in a few weeks, the significant increase in dopamine turnover and the beneficial effect of parenteral administration of GM1 to patients with Parkinson's disease [24] suggest that our treatment method will be particularly useful for patients with Parkinson's disease. It is our sincere hope that other research groups will take note of these findings and extend our observations.…”
Section: Discussionmentioning
confidence: 99%
“…GM1 treatment restored cognitive and motor function and prevented decline in function in a 90 week trial in monkeys (179). In a double-blind, placebocontrolled study, Parkinson's patients improved significantly after 16 weeks of GM1 treatment, compared with both the placebo group and their own initial baselines (180). In addition to GM1, Schneider et al (181) reported potential neuroprotective and neurorestorative roles for the synthetic ceramide analog L-threo-1-phenyl-2- decanoylamino-3-morpholino-1-propanol (L-PDMP) in mouse models of Parkinsonism.…”
Section: Therapeutic Potentials Of Gangliosides In Patients With Admentioning
confidence: 99%
“…GM1 treatment restored cognitive and motor function and prevented decline in function in a 90 week trial in monkeys. In a placebo controlled study, Parkinson's patients improved significantly after 16 weeks of GM1 treatment [77].…”
Section: Discussionmentioning
confidence: 97%